SEL SURYA HIBRID BULK HETEROJUNCTION NANOPARTIKEL ZnO/Cu-FEOFITIN - . Sugianto (Jurnal Biofisika, 2013)
The hybdrid solar cell in bulk-heterojunction form has been fabricated. It was combined among ZnO and chlorophyll derivatives (Cu-Pheophytin) and insertion of CuSCN layer as hole conductor. The hybrid film of ZnO/Cu-pheophytin has a wide absorption spectrum compare with the ZnO film alone. The characterization result of the hybrid film of ZnO/Cu-pheophytin solar cell has fill factor about 55% which indicated an ideal curve of I-V characteristic. Moreover, the conversion efficiency of the cell was 0.3%.